Iron(III) Chloride‐Catalyzed Decarboxylative–Deaminative Functionalization of Phenylglycine: A Tandem Synthesis of Quinazolinones and Benzimidazoles. Issue 13 (11th September 2015) - Kumar, Manoranjan; Richa; Sharma, Sushila; Bhatt, Vinod; Kumar, Neeraj
Abstract The first iron(III) chloride‐catalyzed decarboxylative–deaminative functionalization of phenylglycine with o‐substituted nitroarenes was achieved for the synthesis of 4(3H)‐quinazolinones and benzimidazoles. The reaction of 2‐nitrobenzonitrile/2‐nitro‐N, N‐diphenylamine with phenylglycine at 120 °C in the presence of potassium carbonate as a base in toluene generated the products in 45–87% yields. Various functional groups like nitro, fluoride, chloride and trifluoromethyl were well tolerated under the present reaction conditions. In this tandem approach, involvement of transfer hydrogenation of the nitro functionality with in situ generated ammonia, imination, nitrile hydration to amide and oxidative cyclization sequences have been established. The process avoids the use of an external hydrogen source, costly catalysts as well as the isolation of amine and amide intermediates.